PERAN ASEAN DALAM MENANGGULANGI PEMBAJAKAN KAPAL DI WILAY - hafiza, aryen nur; Lestari, Maria Maya; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The Waters of Southeast Asia have important values for countries in theregion. The waters of Southeast Asia have a very high potential for conflictbecauseof the high activities, so more many a security threat, including the threat of ship piracy. The problmes of ship piracy is still going until today aand mostoften occursin the Malacca Strait, South China Sea, and the Sulu Sea. This type ofresearch wasnormative law. The analysis carried out is a qualitative analysis orresearch that isstated in writing.From the resulted of the researched problem, there were two points thatcan be concluded. First, ASEAN's role in tackling ship piracy was byestablishment of forums and regional cooperation to discussed existing threats. Second, the coastal states’ efforts in tackled ship piracy in the Malacca Straitwere by establisha Malacca Strait Patrol,in the South China Sea by establish theaASEAN Declaration on the South China Sea, and the last in the Sulu Sea by establish a Indomalphi’s Coordinated Patrol. The author's suggestion, First, itwas hoped thatASEAN can make a special rule regarding this crime of ship piracyto overcome it.Second, it was hoped that make a court or tribulal for a hijackers.Keywords: ASEAN, Ship Piracy, Southeast Asia, Malacca Strait Patrol,Indomalphi’s Coordinated Patrol.